EXPLORING TRIBAL IDENTITY IN INDIAN LITERATURE: A FOCUS ON THE TRIBES OF KARNATAKA - Sharan S J (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Tribal identity has been a focal point of analysis and understanding in Indian literature, showcasing the complex interweaving of cultural, social, and historical aspects of tribal societies. This research article examines the depiction and development of tribal identity in Indian literature, specifically focusing on the tribes of Karnataka. By encompassing various genres and linguistic traditions, this analysis explores the portrayal of tribal life, customs, beliefs, and challenges in literary works. The research also investigates the transformation of tribal identity over time, which mirrors changes in societal attitudes, political dynamics, and the impact of technology. The analysis explores the intricacies of tribal identity construction, negotiation, and assertion in Indian literature by examining various literary texts, such as novels, short stories, poetry, and folk tales. This study explores themes of marginalisation, cultural hybridity, and resistance in tribal literature, aiming to enhance our understanding of the complex and diverse landscape of tribal literature while also providing insights into broader issues of identity, diversity, and inclusion in modern society.